Effects of cotrimoxazole prophylaxis on Talaromyces marneffei infection in HIV/AIDS patients receiving antiretroviral therapy: a retrospective cohort study - Junjun Jiang; Fengxiang Qin; Sirun Meng; Eric J. Nehl; Jinping Huang; Yanfen Liu; Jun Zou; Wenyi Dong; Jiegang Huang; Hui Chen; Ning Zang; Bingyu Liang; et al. (Emerging Microbes and Infections)
The dimorphic fungus Talaromyces marneffei (TM) is a common cause of HIV-associated opportunistic infections in Southeast Asia. Cotrimoxazole (CTX) inhibits folic acid synthesis which is important for the survival of many bacteria, protozoa, and fungi and has been used to prevent several opportunistic infections among HIV/AIDS patients. We question whether CTX is effective in preventing TM infection. To investigate this question, we conducted an 11-year (2005–2016) retrospective observational cohort study of all patients on the Chinese national antiretroviral therapy (ART) programme in Guangxi, a province with high HIV and TM burden in China. Survival analysis was conducted to investigate TM cumulative incidence, and Cox regression and propensity score matching (PSM) were used to evaluate the effect of CTX on TM incidence. Of the 3359 eligible individuals contributing 10,504.66 person-years of follow-up, 81.81% received CTX within 6 months after ART initiation, and 4.73% developed TM infection, contributing 15.14/1,000 person-year TM incidence rate. CTX patients had a significantly lower incidence of TM infection than non-CTX patients (4.11% vs. 7.53%; adjusted hazard ratio (aHR) = 0.50, 95% CI 0.35–0.73). CTX reduced TM incidence in all CD4+ cell subgroups (<50 cells/μL, 50–99 cells/μL, 100–199 cells/μL), with the highest reduction observed in patients with a baseline CD4+ cell count <50 cells/μL in both Cox regression and the PSM analyses. In conclusion, in addition to preventing other HIV-associated opportunistic infections, CTX prophylaxis has the potential to prevent TM infection in HIV/AIDS patients receiving ART.